2014
DOI: 10.1007/s00277-014-2223-9
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of platelet transfusion in patients with thrombotic thrombocytopenic purpura: a retrospective case series study

Abstract: Current guidelines advise against the transfusion of platelets in patients with thrombotic thrombocytopenic purpura (TTP) except in cases of life-threatening hemorrhage. We conducted a retrospective medical chart review to examine the outcomes of patients with TTP who received platelet transfusion at our institution from September 2002 to September 2012. A search for "thrombotic thrombocytopenic purpura" in the discharge summary identified 233 patients, out of which only 15 patients had TTP and received platel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
(33 reference statements)
1
7
0
Order By: Relevance
“…Platelet transfusions have previously been considered to be absolutely contraindicated in TTP because of a theoretical risk of platelet‐rich thrombi increasing tissue ischaemia/infarction. This view was supported by early case studies; however, subsequent studies involving larger cohorts have cast doubt over this contraindication . Of note, a common documented reason for platelet transfusion in our cohort was insertion of central venous lines for PEx where platelet transfusion has not shown efficacy in decreasing hemorrhagic complications …”
Section: Discussionsupporting
confidence: 57%
“…Platelet transfusions have previously been considered to be absolutely contraindicated in TTP because of a theoretical risk of platelet‐rich thrombi increasing tissue ischaemia/infarction. This view was supported by early case studies; however, subsequent studies involving larger cohorts have cast doubt over this contraindication . Of note, a common documented reason for platelet transfusion in our cohort was insertion of central venous lines for PEx where platelet transfusion has not shown efficacy in decreasing hemorrhagic complications …”
Section: Discussionsupporting
confidence: 57%
“…Except for life-threatening hemorrhage, platelets infusion is contradicted among TTP patients prior to the introduction of PEX, which exacerbate the severity of microvascular thrombi formation, worsen the patient's condition seriously [16]. Although PEX was used 7 times and rituximab infusion given twice, a patient died in our cohort because of platelet infusion before the diagnosis.…”
Section: Discussionmentioning
confidence: 93%
“…Alternatively, a few case reports suggested that PLT transfusion may be safe . Recent evidence for harm from PLT transfusion in patients with TTP is still uncertain .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study from the University of Pittsburgh Medical Center reported on the adverse events of PLT transfusion in TTP within 24 h of transfusion . The investigators found that of 233 patients with TTP, 15 patients received PLT with 2 deaths beyond 24 h from transfusion.…”
Section: Discussionmentioning
confidence: 99%